Social support and parenting stress in at-risk Portuguese families - Nunes, Lara Ayala (2019)
A Summary: Families that are at psychosocial risk live under personal and contextual circumstances that hinder their parenting skills. They frequently lack the resources necessary for addressing the challenges of parenting and encounter multiple stressful life events. Social support may help diminish the parenting stress that is experienced from living in a disadvantaged environment by enhancing coping strategies. However, previous research examining the associations between parenting stress and social support among at-risk families has been inconclusive. This study analyzed the psychosocial profile of at-risk Portuguese families, the size and composition of their social support networks and the associations between social support and parenting stress. Participants consisted of 167 parents (80% mothers) who received assistance from Child Protection Services. Measures included the Parenting Stress Index-Short Form, the Arizona Social Support Interview Schedule and a socio-demographic questionnaire. Findings: Parenting stress levels were extremely high, with 44.51% of parents showing clinically significant levels. Emotional support was the type of support that was most closely related to parental distress, namely the network size available for providing emotional support (r=-.27, p=.000) and satisfaction with the emotional support received (r=-.24, p=.006). Applications: The size of the emotional support network was significantly smaller among parents who reported clinically significant levels of parenting stress. Hence, having the opportunity to express feelings and concerns as well as engaging in social interactions during leisure time may serve as protective factors against parental stress in at-risk families. Implications of for the interventions of professionals who work with at-risk families are discussed.